Experimental method and application of the slurry “diffusion-bleeding-seepage” of isolated overburden grout injection - Wang, Chaochao; Xu, Jialin; Xuan, Dayang; Li, Jian (Frontiers in Earth Science, 2023)
Isolated overburden grout injection (IOGI) is a green mining method to control surface subsidence. Slurry water significantly influences grouting effectiveness and mining safety. This study establishes a three-dimensional visualization experimental system for slurry “diffusion-bleeding-seepage” to investigate the seepage law of slurry water. The system is composed primarily of a transparent box (1.2 m × 0.5 m × 0.25 m) and support, with the solid–liquid coupling seepage similar material and modules for mining, grouting injection, slurry pressure and displacement monitoring, overburden saturation monitoring, and water leakage monitoring of the working face. A similar material with good permeability and non-disintegration is obtained by hydrophilic, water absorption, and permeability tests. Grouting and mining are simulated by pulling acrylic sheets and pumping slurry. With the fly ash slurry entering the injection layer, the slurry undergoes water–cement separation, and the water bleeding is formed to seep into the similar material. The volumetric water content of the similar material is obtained by arranging multiple groups of volumetric water content sensors into the similar material. The corresponding saturation is obtained by theoretical calculation. The experimental system is used to simulate the seepage of slurry water in a high initial saturation overburden, and the characteristics of injection slurry diffusion and water bleeding are obtained. The profile distribution of seepage of slurry water is found to possess a semi-elliptical shape. Under the condition of high initial saturation, slurry water appears in the working face. The system provides a convenient method for further research of IOGI slurry water seepage.